Nordic contributions in IS research : 8th Scandinavian Conference on Information Systems, SCIS 2017, Halden, Norway, August 6-8, 2017, Proceedings /: 8th Scandinavian Conference on Information Systems, SCIS 2017, Halden, Norway, August 6-8, 2017, Proceedings. (2017) - Unknown
No abstract available